Rules of the safety in the prophetic sunnet and a benefit from it at present time - Alwormely, Farsat A. Y. (Humanities Journal of University of Zakho, 2017)
The research deal s with the rule of safety to witch our prophet Muhammad (Peace be upon him) in his hadiths for the safety and protect of the individuals and society. It aims throughout the above rules to shed light on what the prophetic sunnet pays attention for the purpose of the safety of the human being and lessening the risks and harms which may target them by going extremely in the religions and mundane affairs in the health, psychological, physical and financial fields to avoid occurrence of these accident and risks. Also, the research aims to show how important is to follow up the prophet’s instructions towards the safety, creating safety, security, health, happiness, money and well-being to individuals and society staving them off offensive and risk.